Notes on the genus Streblocera Westwood, 1883 (Hymenoptera: Braconidae: Euphorinae) from Vietnam, with description of four new species - Long, Khuat Dang; Nhi, Pham Thi (Zootaxa, 2020)
Species of the genus Streblocera Westwood are reviewed with four new species from Vietnam described and illustrated, viz. Streblocera (Eutanycerus) intermedia Long, sp. n.; S. (E.) quangbinhensis Long, sp. n.; S. (E.) trangana Long & Pham, sp. n.; and S. (E.) tuyenquangensis Long, sp. n.. A key to Vietnamese species of the subgenus Eutanycerus is provided.